(untitled) (Research, Society and Development, 2022)
Objective: to guide pregnant women and health professionals, about the importance of dental prenatal care, providing a safe pregnancy, showing the consequences of the lack of such care, demystifying what limits treatment and describing simple and continuous educational solutions. Method: research of a descriptive nature, with a qualitative approach, carried out from the bibliographic review of scientific articles available online, with a time frame from 2004 to 2018. After selection, the results of the analysis were categorized, based on the reasoning of the rights established by law and guaranteed through Federal Government programs, through the Ministry of Health. Results: the most frequently detected oral diagnoses during pregnancy involved gingivitis, gingival hyperplasia, pyogenic granuloma, salivary flows and buffering capacity, caries, dental erosions, tooth mobility and periodontitis. A correlation was detected between periodontal diseases and high rates of premature births and/or low birth weight. The gestational biological factor opened precedents and facilitated oral pathologies, which could be minimized with preventive actions that contributed to the containment of diseases. Conclusion: during the gestational period, oral health is directly related to the general health of the mother and fetus. It is extremely important that the pregnant woman has dental care during prenatal care and that consultations are carried out with specialized exams that include teeth, gums, tongue, palate and mucosa.